2019
DOI: 10.1073/pnas.1910095116
|View full text |Cite
|
Sign up to set email alerts
|

Great apes use self-experience to anticipate an agent’s action in a false-belief test

Abstract: Human social life depends on theory of mind, the ability to attribute mental states to oneself and others. A signature of theory of mind, false belief understanding, requires representing others’ views of the world, even when they conflict with one’s own. After decades of research, it remains controversial whether any nonhuman species possess a theory of mind. One challenge to positive evidence of animal theory of mind, the behavior-rule account, holds that animals solve such tasks by responding to others’ beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
106
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 170 publications
(109 citation statements)
references
References 43 publications
2
106
0
1
Order By: Relevance
“…A gold standard for the comparative approach hence involves collecting comparable datasets through the cross-species application of matching experimental paradigms. This strategy has been extremely productive when examining other traits thought to be key to human cognition such as cumulative culture ( 19 ), hyper-cooperation ( 20 ), working memory ( 21 ), and theory of mind ( 22 , 23 ). Here, we undertook such a directly comparative investigation of the evolutionary roots of Non-AD processing by implementing a standardized, auditory artificial grammar learning paradigm in common marmosets ( Callithrix jacchus ), chimpanzees ( Pan troglodytes ), and humans.…”
Section: Introductionmentioning
confidence: 99%
“…A gold standard for the comparative approach hence involves collecting comparable datasets through the cross-species application of matching experimental paradigms. This strategy has been extremely productive when examining other traits thought to be key to human cognition such as cumulative culture ( 19 ), hyper-cooperation ( 20 ), working memory ( 21 ), and theory of mind ( 22 , 23 ). Here, we undertook such a directly comparative investigation of the evolutionary roots of Non-AD processing by implementing a standardized, auditory artificial grammar learning paradigm in common marmosets ( Callithrix jacchus ), chimpanzees ( Pan troglodytes ), and humans.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that infants expected the actor to look for the object in its original location, where she had last seen it. Other behavioral research has found evidence of implicit false-belief understanding in young children (24,28), older infants (26,27), and non-human primates (29,30). Moreover, neuroimaging research has found evidence that infants as young as 6 to 7 months of age represent others' false beliefs when watching videos of others' actions (31,32).…”
Section: The Role Of Theory Of Mind In Children's Moral Evaluationsmentioning
confidence: 99%
“…It is possible, though, that the apes had simply learned that people tend to look for things where they last saw them, and were not considering what the person believed. Kano et al (2019) offer a more exacting test in which the apes saw a video in which an actor saw an object hidden under one of two boxes. The actor then moved behind a barrier that was either translucent or opaque, and the object was shifted to the other box.…”
Section: Theory Of Mindmentioning
confidence: 99%